Atherosclerosis as autoimmune disease - Sima, Petr; Vannucci, Luca; Vetvicka, Vaclav (Annals of translational medicine, 2018)
No attention is usually focused on the possible involvement of immune mechanisms, particularly of autoimmunity, on the development and progress of atherosclerosis. The pioneering work occurring almost 50 years ago was overlooked, and the idea of atherosclerosis as an autoimmune disease only started gaining traction about 10 years ago. Our review discusses the recent findings and offers insights into the possibility that alterations of the immune system play a significant role in the development of atherosclerosis.
Keywords: cholesterol; Atherosclerosis; inflammation; immunity